Pengaruh Pengungkapan Corporate Social Responsibility terhadap Tingkat Profitabilitas Perusahaan - Zalsabila Rahmalia Putri Yuliansyah; Epi Fitriah (Bandung Conference Series: Accountancy, 2022)
Abstract. “Disclosure of Corporate Social Responsibility (CSR) is a form of the company's commitment to social, community and environment around the company's operations which is important to pay attention to in order to get a good image in the eyes of stakeholders. A good image is something that will have a positive impact on the company, such as increasing the level of profitability or profits obtained as a result of investors' trust in the company. This study aims to determine whether there is an effect of Corporate Social Responsibility (CSR) disclosure on the level of profitability proxied by Return On Assets (ROA) and Return On Equity (ROE) in mining sector companies listed on the IDX in 2017-2020. The research sample consisted of 15 companies with a total of 60 observations using purposive sampling technique. The data used in this study are secondary data obtained from www.idx.co.id. Data collection techniques with documentation techniques. Hypothesis testing in this study using simple regression analysis using SPSS 23.0. The results of hypothesis testing show that the disclosure of Corporate Social Responsibility (CSR) and the level of Company Profitability in the mining sector listed on the IDX in 2017 - 2020 fluctuates, disclosure of Corporate Social Responsibility (CSR) affects Return On Assets (ROA) and disclosure of Corporate Social Responsibility ( CSR) has no effect on Return On Equity (ROE)”. Abstrak. “Pengungkapan Corporate Social Responsibility (CSR) merupakan bentuk komitmen perusahaan terhadap sosial, masyarakat dan lingkungan disektiar perusahaan tersebut beroperasi yang penting untuk di perhatikan agar mendapatkan citra baik dimata staakeholder. Citra yang baik merupakan hal yang akan memberikan dampak positif bagi perusahaan seperti meningkatnya tingkat profitabilitas atau laba yang di dapat akibat dari kepercayaan para investor terhadap perusahaan. Penelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh pengungkapan Corporate Social Responsibility (CSR) terhadap tingkat profitabilitas yang diproksikan dengan Return On Asset (ROA) dan Return On Equity (ROE) pada perusahaan sektor pertambangan yang terdaftar di BEI pada tahun 2017-2020. Sampel penelitian terdiri dari 15 perusahaan dengan jumlah pengamatan 60 menggunakan teknik purposive sampling. Data yang digunakan dalam penelitian ini berupa data sekunder yang diperoleh dari www.idx.co.id. Teknik pengumpulan data dengan teknik dokumentasi. Pengujian hipotesis dalam penelitian ini menggunakan analisis regresi sederhana dengan menggunakan SPSS 23.0. Hasil pengujian hipotesis menunjukan bahwa pengungkapan Corporate Social Responsibility (CSR) dan Tingkat Profitabilitas Perusahaan pada sektor pertambangan yang terdaftar di BEI tahun 2017 - 2020 berfluktuasi, pengungkapan Corporate Social Responsibility (CSR) berpengaruh terhadap Return On Asset (ROA) dan pengungkapan Corporate Social Responsibility (CSR) tidak berpengaruh terhadap Return On Equity (ROE)”.